Reinforced biobased adhesive for eco-friendly sandwich panels. (April 2020) - Oliveira, Pablo Resende; May, Michael; Panzera, Tulio Hallak; Scarpa, Fabrizio; Hiermaier, Stefan
Abstract: This work describes the development of a bio-polyurethane (bio-PU) adhesive made from castor oil plant to be used in sustainable (eco-friendly) sandwich panels made from recycled plastic waste. Low-cost fillers, such as Portland cement and recycled rubber particles are incorporated into the biopolymer to modify its mechanical behaviour. Epoxy is also used to benchmark the mechanical performance of the reinforced biopolymer described in this work. A full factorial design is performed to identify the effects of the types of adhesive, particles and their weight fraction on the mechanical and physical properties of hybrid panels. Single lap and adapted T-peel tests are used to assess the adhesion of the polymers to the aluminium surfaces. The inclusion of 3 wt% cement particles in the biopolymer provides a significant increase in the tensile strength and stiffness compared to the pristine bio-PU. Other properties that benefit from that amount of reinforcement in the bio-adhesive are the impact resistance and reduction of density and porosity compared to higher fractions of inclusions. Despite its lower mechanical properties, the biopolymer with rubber particles provides however an increase of the single lap shear strength, the opposite of what happens when using the reinforced epoxy polymer. The T-peel test also highlights the higher bonding affinity of the biopolymer to the sustainable sandwich core; that indicates the promise of using this biopolymer-reinforced adhesive in secondary and sustainable applications.